Perception the Symbolic Scriptures Evaluation and Transformation of Elementary Algebra - Mohammad Hasan, Ban; Jassem Wadi, Kadhum; Abdulameer Abbas, Hayder (International Journal of Psychosocial Rehabilitation, 2020)
The current research work focuses on two areas of unequal importance: symbolic expressions of elementary algebra ("ESA") on the one hand and problem-based discussion ("PBD") situations on the other. The main body of the paper exposes features of structural mottles and didactically plausible ESA systems. It is not a didactical study of algebra in the strict sense, which would be more or less directly applicable to what happens in classrooms, but rather basic research on the structure of symbolic expressions that employ students and teachers in elementary algebra (ESA), intended to serve as a tool for subsequent didactic studies. "Understanding" ESAs means taking into account their syntax, denotation, meaning, and interpretation. According to the meaning we choose, the above statement may mean as well as the understanding of the ESAs is a collective, as the idea that the three components should not be separated. To tell the truth, we adhere to both propositions. However, the proposed study, more specifically, the didactic consequences of the second.